Shuri. Symbiosis - Stone, Nic. (New York, NY : Scholastic Inc., 2022)
The royal palace of Wakanda is one of, if not the most, secure facilities on this planet--or any other. So the anxiety Shuri feels when she's jolted out of sleep by the queen mother with the news that someone attempted to break into the palace--and succeeded--is significant. And as quickly as they broke in, they vanished. The search for this interloper, a mysterious 'symbiote' with superhuman speed and strength, will lead Shuri to the Jabari Lands, a remote, unforgiving part of the country she has never seen. And what she discovers will be more shocking than she could have imagined.
6.2
3-6
Keywords: Shuri -- (Fictitious character) -- Juvenile fiction; Princesses -- Juvenile fiction; Superheroes -- Juvenile fiction; Missing children -- Juvenile fiction; Wakanda (Africa : Imaginary place) -- Juvenile fiction; Plant ecology -- Juvenile fiction; Shuri -- (Fictitious character) -- Fiction; Princesses -- Fiction; Superheroes -- Fiction; Missing children -- Fiction; Wakanda (Africa : Imaginary place) -- Fiction; Plant ecology -- Fiction; Adventure and adventurers -- Fiction; Superhero fiction; Action and adventure fiction; Science fiction